THE ENGAGEMENT OF SECONDARY SCHOOL LEARNERS FOR LEARNING SCIENCE BY RESPONSIBLE RESEARCH AND INNOVATION - Peciuliauskiene, Palmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article deals with the role of responsible research and innovation (RRI) in promoting intrinsic motivation of secondary school learners. RRI is a new concept highlighted by the European Commission that refers to the process which requires a dialogue between scientists and all citizens including the young generation to align the results of research with societal needs in a better way. RRI deals with uncertain areas of knowledge, where arguments and values matter as much as facts. It gives students an opportunity for responsibility and self-expression for coming to informed decisions about the science innovation and their impact. This situation requires a deeper look into the problem of motivation for learning science from the aspect of RRI activity. The research problem is formulated as a question: how does responsible research and innovation in science education promote intrinsic motivation of secondary school learners. Learners’ intrinsic motivation was analysed on the basis of Self-Determination Theory (STD). According to STD, it is important to fulfil three basic psychological needs of learners: the need for autonomy, the need for competence and the need for relatedness. Intrinsic motivation inventory (IMI) was used to assess the participants’ intrinsic motivation related to the RRI activity in science. The article describes the results of RRI project ENGAGE in Lithuania.